Notoscyphus grollei sp. nov. in Bitterfeld amber rather than the extant Notoscyphus lutescens (Lehm. & Lindenb.) Mitt. - Váňa, Jiří; Schäfer-Verwimp, Alfons; Bechteler, Julia; Schmidt, Alexander R.; Heinrichs, Jochen (Phytotaxa, 2015)
A Paleogene fossil of a leafy liverwort that had earlier been assigned to the extant species Notoscyphus lutescens is described as Notoscyphus grollei, sp. nov. It differs from all other Notoscyphus taxa by mammillose-papillose leaf cells.